Physical literacy profiles of elementary school students by gender - Teten Hidayat; Lutfi Nur; Rafdlal Saeful Bakhri (Universitas Suryakancana, 2026)
Physical literacy is an essential outcome of physical education and plays an important role in promoting lifelong engagement in physical activity. This study aimed to describe the physical literacy profiles of elementary school students based on gender. A descriptive quantitative survey was conducted involving 82 students from SDN Cimahi Mandiri 5, consisting of 45 boys and 37 girls. Data were collected using the Physical Literacy in Children Questionnaire (PL-C Quest), which assesses four domains: physical, psychological, social, and cognitive. Data were analyzed using descriptive statistics, including mean, standard deviation, minimum and maximum scores, percentages, and norm-referenced categorization. The results showed that boys demonstrated a higher overall physical literacy score (M = 91.16) than girls (M = 84.95). Overall, most students were categorized at the medium level (41.5%). Across all participants, the social domain obtained the highest mean score (3.02), followed by the physical (3.01), psychological (2.92), and cognitive (2.82) domains. Boys showed higher mean scores in the physical, social, and cognitive domains, whereas girls demonstrated slightly higher scores in the psychological domain. These findings indicate that differences in physical literacy profiles were observed between boys and girls across several domains. The results provide baseline information for designing more adaptive and inclusive physical education programs that accommodate students' characteristics and support the development of physical literacy in elementary schools.